Total flavonoid contents and in silico study of flavonoid compounds from Meniran (Phyllanthus niruri L.) towards alpha-amylase and alpha-glucosidase enzyme - Sri luliana; Rise Desnita; Ronny Martien; Arief Nurrochmad (Pharmaciana, 2019)
Meniran (Phyllanthus niruri L.) is a plant that is reported to contain flavonoids and shows the activity as a type 2 anti-diabetic by a mechanism of inhibiting the absorption of glucose. Flavonoid compounds such as rutin, quercetin and hesperidin shows anti-diabetic activity. This research aims to determine the levels of total flavonoids and docking studies of flavonoids from meniran against α-amylase and α-glucosidase. Analysis of content of total flavonoids utilizes colorimetric method using AlCl3 and routine standard, the docking study uses Autodock Vina (version 1.1.2) program with the assistance of AutoDockTools (ADT) and visualization of docking results using Discovery Study. The results of the determination of total flavonoids level was 12.32 ± 0.53 mgRE/g extract whereas in ethyl acetate fraction and water each were 19.33±0,68 and 20.07±1.23 mgRE/g respectively. Results of all flavonoids dicking study shows the potential to bind to both receptors, rutin has better binding energy towards α-amylase whereas against α-glucosidase is demonstrated by 3-O -β-D-glucopyranosyl-(2-1)-O-β-D-xylopyranoside quercetin.